2016
DOI: 10.1080/17441692.2016.1229354
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors contributing to teenage pregnancy in Zomba district, Malawi

Abstract: This study explores sociocultural and other risk factors associated with unplanned teenage pregnancy in Zomba district of Malawi. Data were obtained from 505 participants under the age of 20 years using a questionnaire administered through face-to-face interviews held at five antenatal clinics. The data were analysed using descriptive statistics, frequency tables and chi-square analysis which allowed comparative understanding of the sociocultural risk factors for planned and unplanned teenage pregnancy in Zomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 16 publications
7
71
2
2
Order By: Relevance
“…Previous studies with different populations support this view. Observational studies have shown several correlations of higher education attainment, noted as educational empowerment with lower chances of adolescence pregnancy [42][43][44]. Conversely, adolescent mothers are less likely to complete formal education [43,45].…”
Section: Educational Empowermentmentioning
confidence: 99%
“…Previous studies with different populations support this view. Observational studies have shown several correlations of higher education attainment, noted as educational empowerment with lower chances of adolescence pregnancy [42][43][44]. Conversely, adolescent mothers are less likely to complete formal education [43,45].…”
Section: Educational Empowermentmentioning
confidence: 99%
“…Sub-Saharan African (SSA) countries have some of the highest rates of early childbearing in the world (Human Rights Watch, 2018;Kaphagawani & Kalipeni, 2017;Omoro et al, 2018;Treffers, 2003;Yakubu & Salisu, 2018), particularly in East Africa with a rate of 21.5% (Kassa et al, 2018). Within the East African Community (EAC), 1 high rates of teenage pregnancy have been reported for Uganda and Tanzania, with 140 and 132 births per 1000 women aged 15-19 years respectively (UNFPA, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Teenage pregnancy is recognised as having many negative consequences: for the girls, their children and for a country's development. Previous research has highlighted poor health outcomes (pregnancy and delivery complications, unsafe abortion, mortality), increased gender inequality and a considerable reduction in economic growth chances (Kaphagawani & Kalipeni, 2017;Laski, 2015;Middleman & Zimet, 2016;Omoro et al, 2018;Wachira et al, 2016). Significantly, teenage pregnancy is a serious concern for and a threat to gender parity in education, as it contributes to girls dropping out of school (Laski, 2015;Middleman & Zimet, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…What follows below is a synopsis of each article under these three overarching themes. The first group on maternal health contains four articles, that is, Okigbo, Adegoke, and Olorunsaiye (2017), Oyibo, Watt, and Weller (2017), Sofolahan-Oladeinde, Conserve, Iwelunmor, Airhihenbuwa, and Gbadegesin (2017) and Kaphagawani and Kalipeni (2017). These four articles examine issues concerning reproductive health indicators, community perceptions of maternal mortality, application of the PEN-3 cultural model to childbearing decision-making of women living with HIV and AIDS, and the problem of teenage pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Kaphagawani and Kalipeni (2017) note that teenage pregnancy is a major health and social problem in Malawi because of its physical, psychological and socio-economic consequences on the teenage mother, her family and the society as a whole. The case study explores risk factors associated with unplanned teenage pregnancy in the Zomba District.…”
Section: Introductionmentioning
confidence: 99%